« Colour is important, we have to start exporting colour » - (:unkn) unknown (My University, 2021)
Around 1970, Agfa-Gevaert sought to conquer new markets in West Africa, especially for its colour films, which were still not widely distributed in this region of the world. The photographer James Barnor was born in 1929 in Ghana and from 1959 to 1969 lived in England where he learned to master the technical skills of colour. As such, he seemed to be the perfect agent to become an Agfa “ambassador” in Ghana. Through his singular trajectory, caught between two poles, this article analyses the arrival of colour in Ghana, which partly re-enacts logics of transfer and local appropriation already known in the history of West African photography. In the end, Agfa’s aims did not match the realities on the ground, and the enterprise was a commercial failure: colour was not taken up until well in the 1970s, mainly because of a lack of resources. Still, James Barnor contributed through it to enriching the modes of representation of the society that surrounded him.
Keywords: African Research